SIMULASI FIBER COUPLER KOMBINASI SERAT MODA TUNGGAL DAN SERAT KISI BRAGG UNTUK KOMPONEN SENSOR OPTIK - Meri, Ros (Komunikasi Fisika Indonesia, 2016)
Fiber coupler was successfully developed by combining single mode fiber and fiber Bragg grating. A characterization of fiber coupler was analyzed based on result simulation by using OptiGrating software with varying long grating 1 Ã104